Ilmu Pengetahuan dan Teknologi Dalam Sudut Pandang Islam - Ariyadi Ariyadi (Jurnal Sains Komputer dan Teknologi Informasi, 2018)
The modern era when we as Muslims in facing on the current challenges of globalization are increasingly conflict to it make use of technology in a good way for it to be beneficial to the people, nation and religion. Already should be the Muslims not only make use of technology, time coding to create new technology. And we show that the Muslims are also able to develop and compete at technology-technology that is reliable, creative and innovative. Tafsir on Al-Qurthubi, this verse is a staple of the Foundation about the attempt of making tools and reasons. Allah Ta'ala has preached about the Prophet David, that he makes US armor, binoculars, and eat of his work itself. While Adam is a farmer, Nuh a Carpenter, a tailor, Luqman and So is the tanners. The above interpretation of Islam advocated to create or use a tool that can facilitate our work. That's the technology, and it turns out that the idea of utilization of this technology is in the Qur'an. The technology does have two sides. He could be beneficial if it is used with the aim of a good, or it could be the enemy if it is used for purposes that are not good.